Perancangan sistem Jarak aman berkendara berbasis aplikasi smart detect - Muhammad Faizin; Muhammad Alfin Abdurachim Putra; Muhammad Bagus Laroybafih (Jurnal Teknik Mesin Indonesia, 2025)
The increase in the number of four-wheeled vehicles is followed by the behavior of people who ignore traffic rules on the highway, resulting in an increase in cases of accidents and traffic violations. Based on the conditions that have been described, the authors are interested in conducting a study on the design of a system that can provide a warning to four-wheeled vehicle drivers. The purpose of this study is to find out how to design a safe distance driving system based on android serial communication, find out how to detect a safe distance on the system, and understand the working principle of a safe driving distance system based on android serial communication. The method used in this study is an experimental method with 3 measuring indicators including the accuracy of measuring the vehicle's distance to the object in front of it, the accuracy of reading the vehicle's distance data to the object in front of it on an Android smartphone, and measuring errors that occur in the system. From the test results, it was obtained that the ultrasonic sensor detects the presence of other vehicles at a distance of less than 2 meters and is transmitted to a smartphone via a Bluetooth connection. The results of the validation test showed that the respondents scored with a percentage of 85% -87.5% in the "Very Good" category. This shows that the application of the system test above can produce a distance detector that is integrated with a smartphone to be more effective.